2016
DOI: 10.1128/aem.00813-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pyrroloquinoline Quinone-Dependent Glucose Dehydrogenase Activity in the Model Rhizosphere-Dwelling Bacterium Pseudomonas putida KT2440

Abstract: Soil-dwelling microbes solubilize mineral phosphates by secreting gluconic acid, which is produced from glucose by a periplasmic glucose dehydrogenase (GDH) that requires pyrroloquinoline quinone (PQQ) as a redox coenzyme. While GDH-dependent phosphate solubilization has been observed in numerous bacteria, little is known concerning the mechanism by which this process is regulated. Here we use the model rhizosphere-dwelling bacterium Pseudomonas putida KT2440 to explore GDH activity and PQQ synthesis, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 44 publications
1
79
0
6
Order By: Relevance
“…However, there is also evidence for global regulation and interconnection with other processes, although the precise mechanisms have not been elucidated yet. Available information suggests the ketogluconate branch plays a role in the control virulence; and An and Moe () showed that Gcd levels varied significantly with the carbon source used by Pseudomonas , showing that expression in glucose was higher than in glycerol, LB and citrate, which was consistent with the requirements in glucose dehydrogenase activity. These authors also showed that gcd expression was downregulated by inorganic phosphate, a demonstration of interconnection among metabolism of different nutrients.…”
Section: Transcriptional Regulators Involved In Pseudomonas Carbohydrmentioning
confidence: 85%
“…However, there is also evidence for global regulation and interconnection with other processes, although the precise mechanisms have not been elucidated yet. Available information suggests the ketogluconate branch plays a role in the control virulence; and An and Moe () showed that Gcd levels varied significantly with the carbon source used by Pseudomonas , showing that expression in glucose was higher than in glycerol, LB and citrate, which was consistent with the requirements in glucose dehydrogenase activity. These authors also showed that gcd expression was downregulated by inorganic phosphate, a demonstration of interconnection among metabolism of different nutrients.…”
Section: Transcriptional Regulators Involved In Pseudomonas Carbohydrmentioning
confidence: 85%
“…Conversely, immobilized P can be remobilized and thus release Pi for plant uptake via biochemical processes mediated by soil microorganisms (Richardson and Simpson, 2011). For example, P solubilizing bacteria can produce low molecular-weight organic acids (OAs) to solubilize sparingly soluble Pi (Oteino et al, 2015;An and Moe, 2016), and P mineralizing bacteria and arbuscular mycorrhizal fungi are capable of hydrolyzing Po via secreting phosphatase (Tan et al, 2013;Cui et al, 2015;Ragot et al, 2016). Microbial biomass P also contributes to the soil P pool and is normally in the form of watersoluble Po after microbial cell lysis (Turner and Haygarth, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For the mobilization of sparingly soluble Pi, P solubilizing bacteria adopt the nonenzymatic mechanisms, mainly via exuding OAs and H 1 (Zaidi et al, 2009;Jones and Oburger, 2011;Hsu et al, 2015). Gluconic acid and 2-ketogluconic acid are the principle soil microbial-derived OAs involved, whose biosynthesis requires the redox cofactor pyrroloquinoline quinone (PQQ) (An and Moe, 2016). Recently, the genes (gcd, gad, pqq) encoding the related enzymes have been investigated (de Werra et al, 2009;Hsu et al, 2015;An and Moe, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In P. putida KT2440, the pqqABCDEFH can at least form two transcripts: the pqqABCDEH and and pqqF ( Figure 4-4 A) The PQQ synthesis is transcriptionally regulated and influenced by growth conditions (Choi et al, 2008;Gliese et al, 2009). It is interesting to notice that the inconsistent results in two publications (An and Moe, 2016;Nikel et al, 2014a), which the same strain P. putida KT2440 grown on DM9 medium with glycerol or glucose as the sole carbon sources. Apparently, it looks like both publications conducted in a similar conditions.…”
Section: P Putida Kt2440 Possesses Five Different Terminal Oxidases mentioning
confidence: 99%